Let's talk about being destructive - Berry, Joy Wilt.; Costanza, John (Chicago : Childrens Press, 1984)
Advises children on avoiding destructiveness caused by curiosity, accident, carelessness or anger.
School Library Journal
3.8
K-3
Keywords: Human behavior -- Juvenile literature; Behavior; Human behavior